Teaching object-oriented systems analysis to non-IT students: A practical experience - Yusop, Nor Iadah (IEEE Computer Society, 2006)

(untitled)
Teaching software development course is not easy even to people with computer science qualification, let alone to those without such background. However, the author personal experience has proven that this is not impossible. This paper aims at sharing the method adopted in teaching object-oriented systems analysis to postgraduate students without academic qualification or experience in information technology or computer science. Most of them are merely end-users to a number of ubiquitous applications software such as word processors. For the said course, three aspects were given special emphasis: concepts and theories familiarization, application of the theories, and familiarization of technical contents. In view of their background, with respect to the aspects addressed, the author would suggest that the method applied in the teaching of systems analysis is considerably successful for they manage to produce the deliverables required with acceptable quality.